Vortices on a pinched sphere - Maciuk, Arkadiusz; Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The vortex motion is a sign of the desire to achieve balance. In the study, vortices described by complex numbers are moved from a sphere into a “squeezed” sphere – where the pair of opposite poles become one – called a pinched sphere or concave disk. Vortices on the pinched sphere reflect what is commonly observed in nature. A family of the pinched spheres very well represents the spatial vortices observed daily in gusts of wind. Stock market zigzags constitute an economic vortex – a spiral on the cone whose equivalent is the pinched sphere
Mathematical Economics, 2016, Nr 12 (19), s. 53-59
Keywords: pinched sphere – concave disk; vortex; complex number